THE INFLUENCE OF ORGANIZATIONAL COMMITMENT AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT PT. EXPRESS MAXIMUM SEMARANG BRANCH, CENTRAL JAVA - Lidya Pricilla; Irma Sari Octaviani (International Journal Multidisciplinary Science, 2025)
This study investigates the impact of Organizational Commitment and Work Discipline on Employee Performance at PT. Express Maximum Semarang Branch, Central Java. The research employs a quantitative approach with multiple linear regression analysis. The population consists of 82 employees, and the entire population was used as the research sample (total sampling method). Data were collected through surveys and processed using statistical analysis to determine the relationship between organizational commitment, work discipline, and employee performance. The results reveal that both organizational commitment and work discipline significantly influence employee performance, with work discipline being the dominant factor. Employees with high commitment exhibit greater loyalty and responsibility, while those with strong discipline tend to be more productive and efficient. The study emphasizes the importance of enhancing commitment through leadership and career development while strengthening discipline through policies and performance evaluation to improve overall productivity.